Efficacy of products for bleaching and whitening under orthodontic brackets - Célia Regina Maio PINZAN-VERCELINO; Suellen Nogueira Linares LIMA; Fernando Félix de Jesus Vieira PEREIRA; Júlio de Araújo GURGEL; Gisele Rodrigues da SILVA; Karina Maria Salvatore de FREITAS (Dental Press Editora, 2022)
ABSTRACT Introduction: Many patients wearing orthodontic appliances request alterations in the shade of their teeth during orthodontic treatment. Objective: This study aimed to evaluate the efficacy of different products for bleaching and whitening under orthodontic brackets. Methods: Seventy bovine incisors were randomly divided into five groups (n = 14): C) non-whitening toothpaste (control); WTsi) hydrated silica whitening toothpaste; WThp) 2% hydrogen peroxide whitening toothpaste; OB) in-office bleaching; and HB) at-home bleaching. Two buccal surface areas were evaluated using the Easyshade spectrophotometer: under the metal bracket (experimental) and around the bracket (control). The paired t-test, ANOVA, and Tukey tests were applied for statistical analysis. Results: Intragroup comparisons showed that in groups C, WThp and HB, there were statistically significant differences in the enamel color changes (ΔEab) between under and around the bracket areas (C - under bracket = 7.97 ± 2.35, around bracket = 2.86 ± 0.81, p< 0.01; WThp - under bracket = 4.69 ± 2.98, around bracket = 2.05 ± 1.41, p< 0.01; HB - under bracket = 7.41 ± 2.89, around bracket: 9.86 ± 3.32, p= 0.02). Groups WTsi, OB and HB presented similar perception of tooth whiteness (ΔWID) between the tested areas. Intergroup comparisons demonstrated that under the bracket area, the color change (ΔEab) was similar for all groups, except WThp (C = 7.97 ± 2.35; WTsi = 8.54 ± 3.63; WThp = 4.69 ± 2.98; OB = 9.31 ± 4.32; HB = 7.41 ± 2.89; p< 0.01). Conclusions: The dental color changes were effective for the products tested in groups WTsi, OB and HB in the presence of metallic orthodontic brackets.